Application of sensors in a commercial airplane - Zainuddin, Muhammad Fikry; Muhammad Muni’m, Raden Muhammad Mu’az; Suhadi, Nur Aishah; Abd Rahman, Muhamad Syafiq; Mohd Yusof, Nurul Hannah; Abdul Rahim, Ruzairi
An airplane is a powered fixed wing aircraft that propelled forward by trust from a jet engine or propeller. Airplanes comes in a variety of sizes, shapes and wing configurations. The broad spectrum of uses for airplanes includes recreation, transportation of goods and people, military and research. Most airplanes are flown by a pilot on board the aircraft but some of it is designed to be remotely or computer controlled. There are two parts to any instrument system which are the sensing mechanism and the display mechanism. Information is relayed from the sensors to the indicators via electricity or direct pressure sensing via pneumatic or oil filler tubes. There have three basic kinds of instruments classified by the job they perform which are flight instrument, engine instrument and navigation instrument. In this paper, a few types of typical instrument will be discussed further.